The cloacin receptor of ColV-bearing Escherichia coli is part of the Fe3+-aerobactin transport system. - Bindereif, A (1982)
Escherichia coli strains which contain the Fe3+-aerobactin transport system specified by the ColV plasmid became deficient in aerobactin-dependent iron transport when they were converted to cloacin-resistant derivatives. An outer membrane protein with a molecular mass of 74,000 daltons was overproduced under iron-limiting growth conditions and was absent in cloacin-resistant mutants. Fe3+-aerobactin protected cells against cloacin. These results suggest that the cloacin receptor protein, controlled by the colV plasmid, also participates in Fe3+-aerobactin transport.